Phase characteristics of the superficial impedance of the plasma-like anisotropic environment in the mode of frequency modulated signals - V. F. Yanushkevich; E. Yu. Zayats (Doklady Belorusskogo gosudarstvennogo universiteta informatiki i radioèlektroniki)
The analysis of the interaction of anisotropic plasma-type layer with electromagnetic waves in the mode of frequency modulated signals is made. The propagation of electromagnetic waves in anisotropic plasma-type layer conducted on the basis of studies of phase characteristics of surface impedance.